ENHANCING STUDENTS’ SPEAKING ABILITY THROUGH DEBATE ACTIVITIES AT DARUSSALAM ISLAMIC BOARDING SCHOOL OF KEPAHIANG - Dedi Efrizal (IAIN Bengkulu, 2016)
Abstract: Enhancing Students’ Speaking Ability through Debate Activities at Darussalam Islamic Boarding School of Kepahiang. This study was carried out to improve the students’ speakingabilitythrough Debate Activitiesin Second Year Students of Darussalam Islamic Boarding School of Kepahiangin academis year 2015-2016. The subjects of this study were consisted of 30 students.The method used in this study was Classroom Action Research ( CAR). The Clasroom Action Research design applied in this study was a collaborative classroom action research. The data shows that in cycle I, students speaking achievement is 0% (excellent), 10% (good), 17% (average), 40% (poor), 34% (very poor). In cycle II the students’ speaking achievement is 7% (excellent), 20% (good), 40% (average), 20% (poor) and 13% (very poor). In cycle III students’ speaking achievement is 13% (excellent), 20% (good), 54% (average), 13% (poor) and 0% (very poor). In conclusion, Debate Activitiescould solve the students’ problems and improve their speaking ability.